Mechanism of Panax notoginseng saponins in the prevention of thrombosis - LI Peijuan, WANG Chunmei, ZHAO Qian (Jichu yixue yu linchuang, 2024)
Panax notoginseng saponins (PNSs) as the extracted bioactive components of Panax notoginseng, have a long history of application in prevention of thrombosis. PNSs down-regulate the expression of inflammatory factors, promoting endothelial cell growth, up-regulating the expression of anticoagulants and vasodilators, and regulating endothelial cell function; With multiple targets at which PNSs inhibit platelet adhesion, release, and aggregation; PNSs maintain the activity of the fibrinolytic system by regulating the dynamic balance of tissue type plasminogen activators and inhibitors; PNSs reduce blood viscosity, improve red blood cell indicators, and inhibit thrombosis through multiple pathways.